Identification of cheating methods in large-scale tests: Islamic education subject matter in the national examination - Niayatulloh, Ahmad; Haikal, Muhammad (ARKA INSTITUTE, 2024)
This study aims to determine item characteristics based on item response theory and identify cheating during the administration of the National Standardised School Examination (USBN) for Islamic religious education at the senior high school level in the 2015/2016 school year in Yogyakarta. The data source consists of 2929 answer sheets from USBN participants in the subject of Islamic Religious Education (PAI) under Package A of the KTSP curriculum. Using a quantitative approach with an ex post facto design, the analysis uses item response theory for item characteristics and person fit and test acceptance methods for identifying cheating. The results show that the PAI USBN test instrument for the 2015/2016 academic year has a moderate average level of difficulty, with a good information function. The Test Acceptance method, which identified 153 cases of knowledge sharing, 891 cases of ignorance sharing and 222 cases of response sharing, proved to be more effective in detecting cheating than the Person Fit method, which identified 2 individuals.